Limites e possibilidades das ações formativas a partir da educação CTSA no caso do cursinho pré-vestibular popular da UFSCar - Nascimento, Edson Ricardo Nunes (Universidade Federal de São Carlos, 2026)
This research aims to investigate how the articulation between Science, Technology, Society, and Environment (STSE) education and Socio-scientific Issues (SSI) can be participatorily constructed with teachers at a popular university prep course, analyzing the potentialities and limits of this integration in the context of UFSCar's Popular University Prep Course (UFSCurso). Drawing on formative processes developed with scholarship teachers enrolled in undergraduate and teacher education programs at UFSCar, and grounded in the principles of participatory action research, we sought to promote pedagogical practices that articulated university entrance exam preparation with students' critical formation. The investigation involved seven formative sessions, focal interviews, and analysis of lesson plans produced by the scholarship teachers. The results reveal significant advances in the teachers' conceptual appropriation of STSE/SSI frameworks, particularly in recognizing the non-neutrality of science and in contextualizing content through local socio-scientific themes. However, structural limitations persist, related to the pressure of the university entrance exam, administrative task overload, and the difficulty of fully materializing the more advanced stages of STSE education — particularly the preparation for sociopolitical action. The research demonstrated that popular prep courses constitute privileged contexts for critical science education, revealing a significant gap in the field of STS studies within non-formal spaces of popular education.
Limits and possibilities of formative actions within STSE education: the case of UFSCar's popular university prep course
Keywords: Questões sociocientíficas; Ensino de ciências; Educação popular; Socio-scientific issues; Science education; Popular education; CIENCIAS HUMANAS::EDUCACAO; 10. Redução das Desigualdades